Prognostic value of soluble ST2 postaortic valve replacement: a meta-analysis. Issue 1 (6th March 2018) - Tse, Gary; Ip, Christina; Luk, King Sum; Gong, Mengqi; Ting, Yan Yee; Lakhani, Ishan; Bazoukis, George; Li, Guangping; Letsas, Konstantinos P; Dong, Mei; Liu, Tong; Wong, Martin C S
Abstract : Objectives: Soluble suppression of tumorigenicity 2 (sST2) is a member of the interleukin-1 receptor family and a modulator of hypertrophic and fibrotic responses. Its prognostic value for patients undergoing aortic valve replacement (AVR) has been examined in prospective studies but to date, there has been no systematic evaluation or meta-analysis on this issue. Methods: PubMed and Embase were searched until 1 October 2017 for studies that evaluated the relationship between sST2 levels and mortality after AVR. Results: A total of 18 and 37 entries were retrieved from both databases, from which four studies were included in the final meta-analysis. In a total of 1154 subjects (50% male, mean age 80±10 years old, mean follow-up 14 months), elevated sST2 levels were significantly associated with a 44% increase in the risk of all-cause mortality (HR 1.44, 95% CI 1.30 to 1.60, p<0.0001; I 2 : 44%). Conclusions: sST2 significantly predicts all-cause mortality in patients who have undergone AVR, but this conclusion is limited by the small number of patients. Larger prospective studies are required to better elucidate its value for risk stratification in this patient population.